Precautionary Saving from Different Sources of Income : Evidence from Rural Pakistan - Adams, Richard H., Jr. (World Bank, Washington, DC, 2013)
Few studies have tried to measure how households in a developing country save from each of the different income sources at their disposal. To help fill that gap, the Author uses five-year panel data to examine how households in rural Pakistan save from each of the seven separate sources of income. The author finds that households save from different sources of income at significantly different marginal rates. For example, the marginal propensity to save from external remittances (0.711) is much higher than that for rental income (0.085). As the precautionary model of saving suggests, the reasons for this relate to uncertainty: income that is more variable, tends to be saved at a higher marginal rate. Faced with incomplete capital, and credit markets, households in rural Pakistan save: for a rainy day" by putting away mainly those sources of income that are more variable, and uncertain.